The golf course as an outdoor classroom—A proof of concept project. Issue 1 (16th March 2022) - Szczepanski, Anders; Strandberg, Maria
Abstract: Pupils' learning experience can be improved if part of the teaching takes place in a natural outdoor environment. Golf courses and the land that surrounds them as outdoor classrooms could become particularly important at a time when most of the world's population lives in urban landscapes and when local areas suitable for outdoor activities are becoming scarce. A consequence of the Coronavirus crisis is higher demand for outdoor activities in the urban landscape, including outdoor teaching. The Swedish National Curriculum advocates the development of cognitive as well as affective competencies and skills, which makes outdoor teaching a natural and integrated part of today's school and education, where outdoor and indoor learning activities complement each other. In this project, at Motala Golf Club, in collaboration with the Smedsby School in Motala, methods for outdoor teaching on golf courses and the most suitable areas of the golf course for use as an outdoor classroom were investigated. A training course for participating teachers was held in autumn 2017, and the children visited their new classroom at the golf course in spring 2018. Through this project, Motala Golf Club has become a pilot model for outdoor teaching on golf courses. The concept of the golf course as an outdoor classroom is being implemented in Stockholm municipality and Jönköping municipality. Core Ideas: Pupils' learning experience is improved if part of the teaching takes place outdoors. Demand for outdoor activities in the urban landscape, including outdoor teaching, is increasing. Golf courses in the peri‐urban landscape can provide high quality outdoor classrooms.